Single- and dual-task balance training are equally effective in youth - Lüder, Benjamin; Kiss, Rainer; Granacher, Urs (Frontiers in psychology, 2018)
Due to maturation of the postural control system and secular declines in motor performance, adolescents experience deficits in postural control during standing and walking while concurrently performing cognitive interference tasks. Thus, adequately designed balance training programs may help to counteract these deficits. While the general effectiveness of youth balance training is well-documented, there is hardly any information available on the specific effects of single-task (ST) versus dual-task (DT) balance training. Therefore, the objectives of this study were i) to examine static/dynamic balance performance under ST and DT conditions in adolescents and ii) to study the effects of ST versus DT balance training on static/dynamic balance under ST and DT conditions in adolescents. Twenty-eight healthy girls and boys aged 12-13 years were randomly assigned to either eight weeks of ST or DT balance training. Before and after training, postural sway and spatio-temporal gait parameters were registered under ST (standing/walking only) and DT conditions (standing/walking while concurrently performing an arithmetic task). At baseline, significantly slower gait speed (p0.05, d=0-0.1) in DT costs for all parameters of secondary task performance during standing and walking. Training produced significant pre-post increases (p=0.001; d=1.47) in secondary task performance while sitting. The observed increase was significantly greater for the ST (p=0.04; d=0.81). For standing, no significant changes were found over time irrespective of the experimental group. We conclude that adolescents showed impaired DT compared to ST walking but not standing. ST and DT balance training resulted in significant and similar changes in DT costs during walking. Thus, there appears to be no preference for either ST or DT balance training in adolescents.
Gesehen am 22.07.2019